The relationship between the role of parents and health workers with indicator healthy lifestyle (PHBS) elementary students in the working area of Pakuan baru health center, Jambi - Fitria Eka Putri; Siti Nurizati N A; Usi Lanita; Hubaybah Hubaybah; Adelina Fitri; Fajrina Hidayati (Lembaga Pengembangan Kinerja Dosen, 2023)
Elementary school children are susceptible to various diseases related to PHBS such as diarrhea, DHF, etc. Currently PHBS in Indonesia is still low. The purpose of this study was to determine the factors related to PHBS in elementary school children in the working area of ​​the Pakuan Baru Health Center, Jambi City, in 2022. This research is quantitative with a cross sectional design. Sampling by simple random sampling, a total sample of 105 fifth grade students. Data collection was carried out using questionnaires and observations. Analysis using the chi-square test. The results of this study indicate that respondents with good PHBS were 64.8%. The results of the analysis show that The role of parents is related to PHBS p=0.003. And the role of health workers is not related to PHBS p=0.227. There is a relationship between the role of parents with PHBS in elementary school children, while the role of health workers is not related to PHBS.